Enhanced passive bat rabies surveillance in indigenous bat species from Germany--a retrospective study. - Juliane Schatz; Conrad Martin Freuling; Ernst Auer; Hooman Goharriz; Christine Harbusch; Nicholas Johnson; Ingrid Kaipf; Thomas Christoph Mettenleiter; Kristin Mühldorfer; Ralf-Udo Mühle; Bernd Ohlendorf; Bärbel Pott-Dörfer; et al. (Public Library of Science (PLoS), 2014)
In Germany, rabies in bats is a notifiable zoonotic disease, which is caused by European bat lyssaviruses type 1 and 2 (EBLV-1 and 2), and the recently discovered new lyssavirus species Bokeloh bat lyssavirus (BBLV). As the understanding of bat rabies in insectivorous bat species is limited, in addition to routine bat rabies diagnosis, an enhanced passive surveillance study, i.e. the retrospective investigation of dead bats that had not been tested for rabies, was initiated in 1998 to study the distribution, abundance and epidemiology of lyssavirus infections in bats from Germany. A total number of 5478 individuals representing 21 bat species within two families were included in this study. The Noctule bat (Nyctalus noctula) and the Common pipistrelle (Pipistrellus pipistrellus) represented the most specimens submitted. Of all investigated bats, 1.17% tested positive for lyssaviruses using the fluorescent antibody test (FAT). The vast majority of positive cases was identified as EBLV-1, predominately associated with the Serotine bat (Eptesicus serotinus). However, rabies cases in other species, i.e. Nathusius' pipistrelle bat (Pipistrellus nathusii), P. pipistrellus and Brown long-eared bat (Plecotus auritus) were also characterized as EBLV-1. In contrast, EBLV-2 was isolated from three Daubenton's bats (Myotis daubentonii). These three cases contribute significantly to the understanding of EBLV-2 infections in Germany as only one case had been reported prior to this study. This enhanced passive surveillance indicated that besides known reservoir species, further bat species are affected by lyssavirus infections. Given the increasing diversity of lyssaviruses and bats as reservoir host species worldwide, lyssavirus positive specimens, i.e. both bat and virus need to be confirmed by molecular techniques.